Emerging NO2 gas sensing on substitutionally doped Fe on NiWO4 SCES insulators - Lee, Jong Hyun; Kang, Se Hwang; Park, Gi Hyun; Kim, Min Young; Ji, Sanghyun; Choa, Ha Eun; Han, Gi Hyeon; Hwang, Jeong Yun; Lee, Seung Yong; Lee, Kyu Hyoung (Frontiers in Chemistry, 2024)
In this study, we demonstrate the emergence of NO2 gas sensing capabilities in the typically non-active NiWO4, a strongly correlated electron system (SCES), by introducing substitutional Fe at the Ni site. NiWO4 typically exhibits strong Coulombic repulsion between Ni atoms, resulting in a large band gap of over 3.0 eV and insulating behavior. This correlated behavior is clearly reflected in the significant increase of band gap when considering the Hubbard U correction for the cations, bringing the theoretical value closer to the observed value. The single-phase Fe0.5Ni0.5WO4 displays a notable shift in the [NiO6] symmetric vibration mode and an increase in magnetization. Additionally, theoretical calculations confirm the preservation of the wide band gap, with the Fe and O levels generated within the band gap. These findings indicate that Fe located in the Ni sites modulate Coulombic repulsion in NiWO4 SCES insulators. Unlike the poor gas-sensing performance of intrinsic NiWO4, Fe0.5Ni0.5WO4 exhibits a significant NO2 response (Rg/Ra) of 11 at 200°C than other gases and a limit of detection (LOD) of 46.4 ppb. This study provides a pathway for realizing gas-sensing performance in strongly correlated electron insulators with large band gaps through the introduction of dopant levels at the cation sites.